2005
DOI: 10.3171/jns.2005.102.5.0897
|View full text |Cite
|
Sign up to set email alerts
|

Independent predictors of morbidity after image-guided stereotactic brain biopsy: a risk assessment of 270 cases

Abstract: Basal ganglia lesions, thalamic lesions, and patients with diabetes were independent risk factors for biopsy-associated morbidity. Hyperglycemia on the day of biopsy predicted morbidity in the diabetic population. Epilepsy did not predispose to biopsy-associated seizure. For deep-seated lesions, increasing the number of biopsy samples along an established track rather than performing a second trajectory may minimize the incidence of morbidity. Close perioperative observation of glucose levels may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
163
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(174 citation statements)
references
References 25 publications
9
163
1
1
Order By: Relevance
“…Our morbidity rate of 4% (temporary or permanent neurologic deficit) corroborates the results of these other large series and also demonstrates that an aggressive sampling technique can be employed without compromising patient safety. This is consistent with the study of Mcgirt et al [23], which found that increasing the number of biopsy samples did not independently impact morbidity if the samples were collected along a single needle trajectory.…”
Section: Safety Considerations In Stereotactic Biopsysupporting
confidence: 92%
See 2 more Smart Citations
“…Our morbidity rate of 4% (temporary or permanent neurologic deficit) corroborates the results of these other large series and also demonstrates that an aggressive sampling technique can be employed without compromising patient safety. This is consistent with the study of Mcgirt et al [23], which found that increasing the number of biopsy samples did not independently impact morbidity if the samples were collected along a single needle trajectory.…”
Section: Safety Considerations In Stereotactic Biopsysupporting
confidence: 92%
“…Brainstem and pineal locations accounted for three of four complications, and this is consistent with the findings of previous authors who correlated morbidity with pineal [18] and deep-seated lesions [23]. In general, relatively small numbers of pineal locations in this and other series make generalization to an accurate risk profile for these lesions difficult.…”
Section: Safety Considerations In Stereotactic Biopsysupporting
confidence: 90%
See 1 more Smart Citation
“…Recently, the literature shows advanced studies regarding the concomitant use of CT, angiography, MRI and computer software allowing the surgeon to create interactive images which will guide him precisely during biopsy, with great preservation of important anatomical and neurovascular structures. This complex system provides accurate diagnosis with low morbidity and mortality rates together with high positivity for both the frame system and the frameless needle guided biopsies 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…vides brain tissue samples for further anatomical and histopathological analysis of minimal lesions, as well as lesions located in deep or eloquent brain sites, having low complication risks given its minimal invasive characteristics 4 . The clinical indication is precise for those cases of unclear diagnosis where the precise nature is not clear.…”
Section: Intracranial Lesions Stereotactic Biopsymentioning
confidence: 99%